Snack Production Planning Strategy using Goal Programming Method - Umama, Nadya; Pradjaningsih, Agustina; Riski, Abduh (Universitas Jember, 2024)
UD Surya Snack Banyuwangi is one of the Banyuwangi snack shops that produces several kinds of snacks such as dry sponge cake, Bagiak, sato, sale, and others. Production at the factory is closely related to meeting market demand. Therefore, factories must carry out production planning so that they can produce products in sufficient quantities to meet market demand. Production planning involves making decisions regarding the number of products produced, resource allocation, and setting up the production process to achieve effectiveness and efficiency in the process. The article based on this research aims to obtain optimization values in production planning to meet market demand using the Goal Programming method. Goal Programming is a method that aims to minimize deviations from all goals by adjusting decision variables to achieve conformity with the specified goals. This research was carried out by direct observation at UD Surya Snack which was in direct contact with the factory owner. The data and information used in this research include production volume, production value, profits, production costs, and labor costs in one month. The data was then modeled using the Goal Programming method to determine decision variables, constraint functions, and objective functions and solved with the help of Excel Solver. The results obtained show that the application of Goal Programming in UD. Surya Snack production planning shows optimal values. The total profit earned was IDR 17.078.000 in one month after deducting production costs and labor costs. The deviation values of all constraints that must be minimized in the objective function have been met.